2019
DOI: 10.1002/joc.6065
|View full text |Cite
|
Sign up to set email alerts
|

Non‐stationary modelling of extreme precipitation by climate indices during rainy season in Hanjiang River Basin, China

Abstract: The extreme precipitation regimes have been changing as the climate system has warmed. Investigating the non-stationarity and better estimating the changes of the extreme precipitation are valuable for informing policy decisions. In this study, two precipitation indices are employed to describe the extreme events, including maximum 5-day precipitation amount (RX5day) and the number of very heavy precipitation days (R20). The generalized additive models for location, scale and shape (GAMLSS) is employed to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Guo et al (2008) found that climate change played a dominant role in the changes of streamflow in the Poyang Lake Basin. At present, some studies have considered the simulation of extreme hydro-meteorological events based on non-stationary model (Hao et al, 2019;Tan and Gan, 2017), yet with limited research efforts on exploring the non-stationary probabilistic characteristics of extreme streamflow under a changing climate. Therefore, the study of extreme streamflow frequency analysis under the conditions of climate change is of great importance for ecological environment management and water resources planning in the basin.…”
mentioning
confidence: 99%
“…Guo et al (2008) found that climate change played a dominant role in the changes of streamflow in the Poyang Lake Basin. At present, some studies have considered the simulation of extreme hydro-meteorological events based on non-stationary model (Hao et al, 2019;Tan and Gan, 2017), yet with limited research efforts on exploring the non-stationary probabilistic characteristics of extreme streamflow under a changing climate. Therefore, the study of extreme streamflow frequency analysis under the conditions of climate change is of great importance for ecological environment management and water resources planning in the basin.…”
mentioning
confidence: 99%
“…Tharu and Dhakal [84] also used Bayesian quantile regression to explore the effects of ENSO and NAO on the extreme precipitation at different quantile levels in the United States. Hao et al [85] analyzed the non-stationarities in extreme precipitation events and related climate indices at 13 stations in the Hanjiang river basin, based on the generalized additive model (GAMLSS). They found that better performance of simulating extreme precipitation intensity and scale after considering climate indices.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nonstationary analysis of hydrologic time series has been attracting increasing attention and numerous studies have been reported which attempt to address frequency analysis with the consideration of nonstationarity (Galloway 2011;López & Francés 2013;Panagoulia et al 2014;Hao et al 2019b). The most common ways to analyze nonstationarity of hydrologic time series are to associate the distribution parameters with time by linear relationship in changing environment (Villarini et al 2010;Xu & Huang 2011;Zhang et al 2014;Mullan et al 2016), but unfortunately cannot help to reveal the physical mechanisms behind the changing properties.…”
Section: Introductionmentioning
confidence: 99%
“…The irrationality of this method is that the different trends such as rising, falling and jumping identified based on the historical observations cannot be revealed in the future, making their usefulness to understand the risks of future extreme events limited. To date, many studies have reported that the distribution parameters of candidate probability distribution, in terms of extreme precipitation, flood event, extreme water level and drought event, are dependent on time (Cunderlik & Ouarda 2006) or some physical covariates (e.g., climate indices, urbanization and water reservoir construction; see, for example, Zhang et al 2015b;Liu et al 2017;Hao et al 2019b). Moreover, Hao et al (2019b) and Zhang et al (2015b) pointed out that adopting the physical factors as covariates in modeling the hydrologic events can better describe the changing properties of hydrological events and understand the physical mechanisms behind the changing properties.…”
Section: Introductionmentioning
confidence: 99%